Beyond coverage: improving the quality of antenatal care delivery through integrated mentorship and quality improvement at health centers in rural Rwanda - Anatole Manzi; Laetitia Nyirazinyoye; Joseph Ntaganira; Hema Magge; Evariste Bigirimana; Leoncie Mukanzabikeshimana; Lisa R. Hirschhorn; Bethany Hedt-Gauthier (BMC, 2018)
Abstract Background Inadequate antenatal care (ANC) can lead to missed diagnosis of danger signs or delayed referral to emergency obstetrical care, contributing to maternal mortality. In developing countries, ANC quality is often limited by skill and knowledge gaps of the health workforce. In 2011, the Mentorship, Enhanced Supervision for Healthcare and Quality Improvement (MESH-QI) program was implemented to strengthen providers' ANC performance at 21 rural health centers in Rwanda. We evaluated the effect of MESH-QI on the completeness of danger sign assessments. Methods Completeness of danger sign assessments was measured by expert nurse mentors using standardized observation checklists. Checklists completed from October 2010 to May 2011 (n = 330) were used as baseline measurement and checklists completed between February and November 2012 (12-15 months after the start of MESH-QI implementation) were used for follow-up. We used a mixed-effects linear regression model to assess the effect of the MESH-QI intervention on the danger sign assessment score, controlling for potential confounders and the clustering of effect at the health center level. Results Complete assessment of all danger signs improved from 2.1% at baseline to 84.2% after MESH-QI (p <  0.001). Similar improvements were found for 20 of 23 other essential ANC screening items. After controlling for potential confounders, the improvement in danger sign assessment score was significant. However, the effect of the MESH-QI was different by intervention district and type of observed ANC visit. In Southern Kayonza District, the increase in the danger sign assessment score was 6.28 (95% CI: 5.59, 6.98) for non-first ANC visits and 5.39 (95% CI: 4.62, 6.15) for first ANC visits. In Kirehe District, the increase in danger sign assessment score was 4.20 (95% CI: 3.59, 4.80) for non-first ANC visits and 3.30 (95% CI: 2.80, 3.81) for first ANC visits. Conclusion Assessment of critical danger signs improved under MESH-QI, even when controlling for nurse-mentees' education level and previous training in focused ANC. MESH-QI offers an approach to enhance quality of care after traditional training and may be an approach to support newer providers who have not yet attended content-focused courses.